Permanent disposal of Cs ions in the form of dense pollucite ceramics having low thermal expansion coefficient - Mia Omerašević; Miodrag Lukić; Marjetka Savić-Biserčić; Andrija Savić; Ljiljana Matović; Zvezdana Baščarević; Dušan Bučevac (Nuclear Engineering and Technology, 2020)
A promising method for removal of Cs ions from water and their incorporation into stable crystal structure ready for safe and permanent disposal was described. Cs-exchanged X zeolite was hot-pressed at temperature ranging from 800 to 950 °C to fabricate dense pollucite ceramics. It was found that the application of external pressure reduced the pollucite formation temperature. The effect of sintering temperature on density, phase composition and mechanical properties was investigated. The highest density of 92.5 %TD and the highest compressive strength of 79 MPa were measured in pollucite hot-pressed at 950 °C for 3 h. Heterogeneity of samples obtained at 950 °C was determined using scanning electron microscopy. The pollucite hot-pressed at 950 °C had low linear thermal expansion coefficient of ∼4.67 × 10−6 K−1 in the temperature range from 100 to 1000 °C. Keywords: Cs disposal, Ion exchange, Zeolite, Hot pressing, Thermal expansion